Development JEJAKATUA Using Auto-Stitching as a Campus Virtual Tour to Support Digital Promotion Media - Tri Lathif Mardi Suryanto; Nur Cahyo Wibowo (Future Science, 2020)
In the current millennial era, the digitalization of promotions offers abundant potential so that each agency is competing to attract public attention through the development of promotional digitization. East Java